Computerized adaptive testing : theory and practice - Linden, Wim J. van der; Glas, Cees A. W. (Kluwer Academic, 2000)
Modern computer technology has opened up several new possibilities for optimizing the administration of educational and psychological tests. In computer adaptive testing (CAT), tests are automatically tailored to the proficiency level of the individual examinees. Currently, nearly all large-scale testing programs in the western world are already adaptive or in the process of becoming so. Written by active CAT researchers from Europe and North America, the chapters offer a comprehensive introduction to the latest developments in the theory and practice of CAT. The book can be used both as a basic reference on the state of the art in CAT and a valuable resource in graduate courses on test theory. The theoretical chapters in this book cover such topics as item selection and ability estimation, item pool development and maintenance, item calibration and model fit, and testlet-based adaptive testing. The practical chapters describe the operational aspects of existing large-scale CAT programs.